INOVASI PEMBELAJARAN BAHASA ARAB: MENINGGALKAN CARA LAMA DAN MENYAMBUT ERA BARU - Farhan, Muhammad; Peblian, Lexi (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
This article discusses the innovation in Arabic language learning, covering various important aspects such as the essence of learning innovation, the concept of curriculum innovation, and the application of technology in Arabic language learning. Learning innovation aims to improve the effectiveness and efficiency of the teaching and learning process by utilizing various methods, approaches, resources, and relevant technologies. One of the important innovations in Arabic language learning is the use of technology, such as mobile applications, e-learning platforms, and multimedia, which can enhance student motivation and engagement. However, despite the numerous benefits, the implementation of technology also faces challenges, such as unequal access, teacher readiness, and student adaptation to new methods. Therefore, the development of innovation in Arabic language learning in the digital era is crucial for improving the quality of education, despite facing several obstacles. تتناول هذه المقالة ابتكار تعلم اللغة العربية، مع التركيز على جوانب مهمة مثل جوهر ابتكار التعلم، مفهوم ابتكار المناهج الدراسية، وتطبيق التكنولوجيا في تعلم اللغة العربية. يهدف ابتكار التعلم إلى تحسين فعالية وكفاءة عملية التعليم والتعلم من خلال الاستفادة من مختلف الأساليب والنهج والموارد والتقنيات المناسبة. أحد الابتكارات المهمة في تعلم اللغة العربية هو استخدام التكنولوجيا، مثل التطبيقات المحمولة، منصات التعلم الإلكتروني، والوسائط المتعددة، التي يمكن أن تعزز من تحفيز الطلاب ومشاركتهم. ومع ذلك، وعلى الرغم من الفوائد العديدة، تواجه تطبيقات التكنولوجيا أيضًا تحديات مثل التفاوت في الوصول إليها، استعداد المعلمين، وتكيف الطلاب مع الأساليب الجديدة. لذلك، فإن تطوير الابتكار في تعلم اللغة العربية في عصر الرقمية أمر بالغ الأهمية لتحسين جودة التعليم، رغم مواجهة العديد من العقبات.